The Effect of Procedural and Technological Security Countermeasures on the Propensity to Misuse Medical Data. Issue 2 (3rd April 2017) - Arunothong, Wachiraporn; Nazareth, Derek L.
ABSTRACT: As healthcare providers seek to comply with HIPAA and endeavor to secure their data from external breaches, they also need to realize that another threat to misuse of this data is inappropriate internal use by employees. Not all instances of misuse constitute a HIPAA violation, but they have the potential to become one. Medical data misuse by employees can be alleviated and curbed through the appropriate use of procedural and technological countermeasures. This paper seeks to determine whether electronic health records (EHR) policy and auditing procedures play a role in the propensity of providers to misuse medical data. Through an on-line survey of US physicians, nurses, medical students, and nursing students, using four case vignettes representing various forms of misuse, this research found that providers who were more aware of institutional security policy were more likely to adhere to policies than their counterparts who were not similarly informed. Likewise, providers who believed that their organizations monitored their EHR usage were less likely to engage in misuse than their counterparts who believed they were not monitored. The findings underscore the need for healthcare organizations to emphasize the importance of HIPAA compliance, and inform employees about the steps that the institution takes to maintain compliance, both from a procedural as well as technological standpoint. This study suggests that increasing the awareness of security and policy measures among employees is a vital part of preventing misuse.